2022
DOI: 10.1007/s10654-021-00833-6
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal abnormalities and the risk for gastroesophageal cancers—a histopathology-register-based study in Sweden

Abstract: Background The poor survival of patients with gastroesophageal cancers may improve if additional esophageal precursor lesions to Barrett’s esophagus and squamous dysplasia are identified. We estimated the risk for gastroesophageal cancers among patients with various histopathological abnormalities in the esophagus, including Barrett’s esophagus, subdivided by histopathological types. Methods Histopathology data from esophageal biopsies obtained 1979–2014 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Furthermore, it has been suggested that inflammation triggered by infections is a notable cause of cancer (40,41). Increasing evidence has shown that inflammation is the main cause of EC induction (19). In the present study, the inflammatory inducer LPS (42,43) was used to promote inflammation in EC cells, which simulated the inflammatory response of EC cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, it has been suggested that inflammation triggered by infections is a notable cause of cancer (40,41). Increasing evidence has shown that inflammation is the main cause of EC induction (19). In the present study, the inflammatory inducer LPS (42,43) was used to promote inflammation in EC cells, which simulated the inflammatory response of EC cells.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that the development of EC is a multistep pathogenic process from inflammation to cancer (18,19). The malignant degree of EC is positively associated with inflammatory factors, such as tumor necrosis factor α (TNF-α) (20), and the survival time of patients with EC has been confirmed to be negatively correlated with inflammation (21,22).…”
Section: -Methoxydalbergione Inhibits Esophageal Carcinoma Cell Proli...mentioning
confidence: 99%